UPAYAÂ MENUMBUHKANÂ KREATIVITASÂ ANAKÂ DENGANÂ Â PERMAINANÂ MATEMATIKA - achmad hidayatullah (Universitas Muhammadiyah Surabaya, 2016)
TheÂ developmentÂ ofÂ moreÂ advancedÂ affectsÂ parents.Â MostÂ parentsÂ wishedÂ forÂ her cleverÂ countingÂ etc.Â BecauseÂ demandÂ isÂ soÂ greatÂ wouldÂ beÂ aÂ problemÂ ifÂ theÂ expectations imposedÂ onÂ earlyÂ childhoodÂ inÂ aÂ spanÂ ofÂ 2â€7Â years.Â EducationalÂ institutionsÂ alsoÂ as playgroupÂ asÂ Â theÂ ageÂ ofÂ arithmeticÂ thatÂ isÂ notÂ appropriateÂ forÂ children.Â BecauseÂ on the oneÂ hand,Â earlyÂ childhood,Â stillÂ inÂ play.Â ButÂ bothÂ ofÂ themÂ canâ€™tÂ beÂ disputedÂ andÂ faced resistance.Â AÂ BothÂ ofÂ themÂ Â canÂ beÂ bridgedÂ byÂ theirÂ mathematicalÂ educationalÂ gamesÂ in orderÂ toÂ enhanceÂ theÂ creativityÂ ofÂ children.Â SoÂ inÂ earlyÂ childhoodÂ shouldÂ beÂ targetedÂ not cognitiveÂ intelligenceÂ butÂ theÂ creativityÂ ofÂ children.Â Therefore,Â thisÂ studyÂ willÂ focusÂ howÂ to fosterÂ theÂ creativityÂ ofÂ childrenÂ withÂ mathÂ games.Â TheÂ approachÂ inÂ thisÂ studyÂ usingÂ literatif study.Â IsÂ toÂ findÂ variousÂ referencesÂ toÂ giveÂ anÂ answerÂ toÂ theseÂ problems. Â Keywords:Â Education,Â CreativityÂ andÂ MathematicsÂ games